2020
DOI: 10.1038/s41598-020-58095-3
|View full text |Cite
|
Sign up to set email alerts
|

The prostaglandin receptor EP2 determines prognosis in EP3-negative and galectin-3-high cervical cancer cases

Abstract: Recently our study identified EP3 receptor and galectin-3 as prognosticators of cervical cancer. The aim of the present study was the analysis of EP2 as a novel marker and its association to EP3, galectin-3, clinical pathological parameters and the overall survival rate of cervical cancer patients. Cervical cancer tissues (n = 250), as also used in our previous study, were stained with anti-EP2 antibodies employing a standardized immunohistochemistry protocol. Staining results were analyzed by the iRS scores a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…PTGER2 expression increases while PTGER3 expression decreases during cervical neoplasia development [ 118 , 123 ], suggesting these receptors might be considered as positive and negative prognostic markers of cervical cancer lesions, respectively. PTGER2 expression is a prognostic factor for the overall survival in the subgroup of negative PTGER3, and high galectin-3 expressed cervical cancer patients [ 124 ]. PTGER3 signaling promotes the migration of cervical cancer cells through the modulation of the urokinase-type plasminogen activator receptor [ 125 ].…”
Section: Role Of the Axis Cyclooxygenases/pge 2 An...mentioning
confidence: 99%
“…PTGER2 expression increases while PTGER3 expression decreases during cervical neoplasia development [ 118 , 123 ], suggesting these receptors might be considered as positive and negative prognostic markers of cervical cancer lesions, respectively. PTGER2 expression is a prognostic factor for the overall survival in the subgroup of negative PTGER3, and high galectin-3 expressed cervical cancer patients [ 124 ]. PTGER3 signaling promotes the migration of cervical cancer cells through the modulation of the urokinase-type plasminogen activator receptor [ 125 ].…”
Section: Role Of the Axis Cyclooxygenases/pge 2 An...mentioning
confidence: 99%
“…In another example, prostaglandin receptor EP2 (Class A, lipid receptor family) activation was shown to protect against ER stress-induced apoptosis via cAMP-mediated downregulation of p53 and its target gene PUMA [ 72 ]. Elevated EP2 signaling is associated with breast cancer [ 73 ], cervical cancer [ 74 ], and bladder cancer [ 75 ]. High expression of AGTR1 is also associated with metastasis of multiple cancer types and is negatively correlated with the prognosis of ovarian cancer.…”
Section: Ers In Cancermentioning
confidence: 99%
“…10 EP2 has proven to be beneficial to stimulate tumor vascular endothelial cell growth, promote tumor cell invasion and metastasis in the development of various tumors. 11,12 In addition, our previous studies found that butaprost, a selective EP2 receptor agonist, can significantly stimulate the proliferation and invasion of HCC cells. 13 However, whether the precise mechanism of GRK2 involving in HCC is related with EP2 receptor remain to be elucidated.…”
Section: Introductionmentioning
confidence: 97%